Perspektif Kepala Sekolah dalam Penerapan Pendekatan Deep Learning di Sekolah Dasar - Suci Tuningsih; Suci Tuningsih (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
Deep learning is one of the approaches used as a relevant instructional strategy to promote meaningful learning and students’ conceptual understanding in elementary schools. Its success is determined not only by classroom practices but also by the principal’s role as an instructional leader. This study aims to examine principals’ perspectives on the implementation of deep learning in elementary school instruction. The research employed a descriptive qualitative approach with five elementary school principals in Sedayu District as the research subjects. Data were collected through semi-structured and in-depth interviews, school observations, and documentation. Data analysis was conducted using thematic analysis based on the Miles and Huberman model. The findings indicate that principals perceive deep learning as an instructional approach that emphasizes deep understanding and the meaningfulness of students’ learning. Principals play a strategic role in supporting the implementation of deep learning through academic policies, instructional supervision, and providing opportunities for teachers to innovate. However, the implementation of the deep learning approach still faces challenges, including teachers’ readiness, limited instructional time, and administrative workload. This study underscores the importance of principal leadership in creating a learning ecosystem that supports deep learning in elementary schools. By highlighting principals’ perspectives as instructional leaders in policy formulation, academic supervision, and strengthening institutional support, this study contributes novelty by expanding deep learning research from the perspective of school leadership in elementary education.